Gabrina the whore: art and nature in the body of the text - Groves, David (Spunti e Ricerche, 2016)
The aesthetic of art imitating nature applies, with whatever ironic qualifications, only to the signified - the characters and their actions in society. At the level of the signifier, however, art - at least the literary art of a constant reviser and rewriter - may be diametrically opposed to nature. Whereas authors, readers and audience grow old and die, a work of literature may be rewritten against the current of time until it is better than new, at once rejuvenated and more lasting than bronze.